Clonal evaluation of new ornamental pineapple hybrids to use as cut flowers - Costa Junior, Davi Silva; Souza, Everton Hilo; Costa, Maria Angélica Pereira de Carvalho; Pereira, Márcio Eduardo Canto; Souza, Fernanda Vidigal Duarte (Acta Scientiarum. Agronomy, 2016)
Embrapa Cassava and Fruits has developed ornamental pineapple hybrids for several categories of ornamental use including cut flowers, potted plants and landscaping. The objective of this study was to carry out a clonal evaluation of two ornamental hybrids using quantitative and qualitative morphological descriptors to recommend these hybrids as new ornamental pineapple cultivars. Twenty plants of each hybrid (PL01 and PL04) were evaluated regarding the response to floral induction as well as the stability and homogeneity of the clones in two production cycles. The descriptive statistics were calculated and analyzed to determine the genetic distance based on the Gower algorithm. Four groups were formed, two using parental data and the other two containing the different hybrids that were evaluated in the two growing cycles. In the floral evaluation, the time from field planting to harvest of the stem as a cut flower was determined to be as long as 17 months in the first cycle and 13.5 months in the second cycle for both hybrids. They were characterized as a novelty in the flower market; they showed genetic stability and homogeneity and can be recommended as new cultivars of ornamental pineapple because they exhibit satisfactory quality and meet the market requirements.